P245 Development and validation of a Simplified Magnetic Resonance Index of Activity (sMaARIA) for Crohn's disease. (16th January 2018) - Ordas, I; Rimola, J; Alfaro, I; Rodriguez, S; Castro, J; Gallego, M; Giner, A; Barastegui, R; Vara, A; Masamunt, M; Ricart, E; Panes, J
Abstract: Background: The MaRIA index is the best-characterised Magnetic Resonance Enterography (MRE) index for the assessment of luminal Crohn's disease (CD) activity. However, a number of limitations had been recognised. The aim of this study was to develop and to validate a simplified and accurate Magnetic Resonance Index of activity (sMaRIA) for assessing disease activity and therapeutic response of luminal CD. Methods: MRE data from 98 patients, including active and inactive segments (colon and terminal ileum), from two prospective studies were re-analysed to develop the sMaRIA using endoscopy (CDEIS) as gold standard. Further analysis of responsiveness and reliability, in an independent cohort of 37 patients who underwent MRE and endoscopy before and after a therapeutic intervention was performed. Comparison of the diagnostic performance between the original MaRIA and sMARIA for detecting active/severe lesions was performed. Results: Logistic regression analysis showed that wall thickness >3 mm, presence of oedema, ulcers and perienteric fat stranding were independent predictors of disease activity and were used therefore as descriptors of sMaRIA. The sensitivity and specificity of sMaRIA at segment level for detecting active disease using a cut-off point ≥1 were 90% and 81% (AUC 0.91, 95% CI 0.88–0.94), and for detecting severe lesions (ulcers) using a cut-off point ≥2 were 85% and 92% (AUC 0.94, 95% CI 0.91–0.96), respectively. Correlation between sMaRIA and CDEIS/MaRIA was excellent (r = 0.84 and r = 0.97, respectively; p < 0.001). There were no differences with regard to diagnostic performance between the sMaRIA and the original MaRIA for detecting active disease ( p = 0.7) and severe disease ( p = 0.5). The sMaRIA accurately detected changes in lesion severity in response to a therapeutic intervention and was as reliable as endoscopy for the assessment of mucosal healing. Conclusions: Simplified MaRIA index allows a faster and easier assessment of inflammation in CD by keeping high accuracy for both diagnosis and therapeutic response. Main advantages over MaRIA includes a less time consuming calculation and that it is not confounded by missing segments.